Improving Decision Support for Infectious Disease Prevention and Control Aligning Models and Other Tools with Policymakers' Needs - Manheim, David (RAND Corporation, 2016)
This report provides an overview of decision-support tools, including models and nonmodeling approaches, to inform both modelers and policymakers. It offers ways to use these tools to help address real-world policy questions related to infectious disease prevention, detection, control, and response and recommends best practices for technical experts and policymakers to collaborate in developing and using the tools.